O LUGAR DA PSICOLOGIA NA MEDIAÇÃO JUDICIAL - Sand, Adriana P. V. D.; Avila, Patricia M. d.; Avila, Cassiana A.; Schonardie, Elisiane; Campos, Iris F. A.; Souza, Tania M. d. (Salão do Conhecimento, 2013)
Resumo